Long-term rice-crab coculturing leads to changes in soil microbial communities - Ma, Liang; Yang, Tiexin; Dong, Liqiang; Pan, Zhengyan; Feng, Yingying; Li, Zhiqiang; Sun, Fuyu (Frontiers in Microbiology, 2025)
PurposeIn order to investigate the effects of a rice-crab coculture mode and its duration on the richness and diversity of the soil microbial community.MethodSoil from long-term rice-crab coculture mode (MY), newly established rice-crab coculture mode (OY) and rice monoculture mode (N) were used to measured soil physicochemical properties, enzyme activity and 16S and ITS soil microbial communities.ResultsThe results revealed that in terms of mode, the MBC, MBN and CAT of OY were significantly greater than those of N by 10.75, 23.47 and 30.71% (p < 0.05), respectively. The richness and diversity of the soil microbial communities changed little, and there was no difference in the main species. In terms of duration, the OM, SC and PPO contents of MY were significantly greater than those of OY by 21.96, 41.89 and 11.52% (p < 0.05), respectively. The soil fungi changed significantly, and the main species were Mortierella and Pseudeurotium in genus level. The soil physicochemical properties and soil enzymes explained 93.38 and 93.66%, respectively, of the variation in the soil microbial community, and OM and DHA were the main factors influencing the change in soil biodiversity.ConclusionOur results suggested that long-term rice-crab coculture mode altered the richness and diversity of the soil microbial community and soil carbon sequestration.